THE IMPLEMENTATION OF BUILDING KNOWLEDGE OF HE FIELD (BKOF) IN TEACHING NARRATIVE TEXT - Rahmawati, Titin; Fajriah , Yustika Nur (English Education and Applied Linguistics Journal (EEAL Journal), 2023)
This research investigated the implementation of Building Knowledge of the Field (BKOF) in teaching narrative text. The purpose to conduct the research is to examine how does an English teacher implement BKOF in teaching narrative text. While this research uses qualitative applying descriptive study. In the research process, data collection was obtained from observation, document analysis, and interview. Thh result shows that there are four stages to implement Building Knowledge of the Field in teaching narrative text, include: First, the teacher gives stimulus to students, the stimulus given by the teacher is by giving examples of narrative texts and using questions; Second, the teacher guides students to mark vocabulary and sentence patterns which are linguistic elements of narrative text; Third, the teacher asks the students to reconstruct the narrative text which has vocabulary and sentence pattern errors; Fourth, the teacher evaluates the results of students' answers with the students.